The impact of self-efficacy and acculturation on the mathematics performance of immigrant students or minority students with an immigrant background in an urban high school - Li, Evangeline (Kansas State University, 2024)
This dissertation investigated the academic performance of immigrant high school students in urban settings, focusing specifically on mathematics. Drawing on Bandura's self-efficacy theory and Zea and colleagues' acculturation framework, the study explored the complex interplay between sources of self-efficacy, acculturation dimensions, and other factors in relation to academic outcomes. The research encompassed urban high school students in a U.S. northeastern region, employing regression analysis for quantitative insights. The findings revealed and underscored the significant impact of particular sources of self-efficacy on academic performance, emphasizing their pivotal role. Acculturation dimensions displayed varied correlations, urging educators to recognize and integrate students' cultures of origin. The study also indicated the importance of tailored support, cultural responsiveness, and awareness of potential biases in various aspects. This dissertation contributed theoretical, methodological, research, and practical insights that deepen academic understanding and guide educators, administrators, and policymakers in fostering a more equitable and supportive learning environment for immigrant students.
Keywords: Self-efficacy; Acculturation; Mathematics performance; Immigrant students; Correlational study; Urban school